Incorporation of piperazino functionality into 1,3-disubstituted urea as the tertiary pharmacophore affording potent inhibitors of soluble epoxide hydrolase with improved pharmacokinetic properties - Huang, Shao-Xu (2010)
The inhibition of the mammalian soluble epoxide hydrolase (sEH) is a promising new therapy in the treatment of hypertension, inflammation and other disorders. However, the problems of limited water solubility, high melting point and low metabolic stability complicated the development of 1,3-disubstituted urea-based sEH inhibitors. The current study explored the introduction of the substituted piperazino group as the tertiary pharmacophore, which resulted in substantial improvements in pharmacokinetic parameters over previously reported 1-adamantyl-urea based inhibitors while retaining high potency. The SAR studies revealed that the meta- or para-substituted phenyl spacer, and N(4)-acetyl or sulfonyl substituted piperazine were optimal structures for achieving high potency and good physical properties. The 1-(4-(4-(4-acetylpiperazin-1-yl)butoxy)phenyl)-3-adamantan-1-yl urea (29c) demonstrated excellent in vivo pharmacokinetic properties in mice: T(1/2) =14 h, Cmax = 84 nM and AUC = 40200 nM • min with an IC(50) value of 7.0 nM against human sEH enzyme.